Analisis Prosedur Pembayaran Utang Supplier di Hotel X - Septiani, Ni Kadek; Widawati, Ida Ayu Putri; Septiviari, Anak Agung Istri M. (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this research is to determine the procedure for paying supplier debts on accounts payable for the period January-December 2023 at Hotel X. The data analysis technique used in this research is descriptive qualitative based on data collection from interviews and observations. This research was motivated by the delay in payment of debts to suppliers. The research conducted at Hotel X revealed that delays in debt payments were caused by the fact that the procedures for paying debts to suppliers at Hotel X were not implemented according to the concept. The receiving department does not provide a received stamp on the invoice, there is a price adjustment on the invoice so the payable account cannot record the invoice. There is no cost controller, so no one checks the documents before they are submitted to the accounts payable department. The Accounts Payable section delays several tasks, such as not completing supporting documents when recording debts. The cashier's department is not involved in making payments to suppliers, so the accounts payable department has more responsibility. This research helps to provide management with suggestions and solutions to minimise the problems and impacts that occur so that objectives can be achieved.